Analysis of Critical Success Factors in Information Technology Project Management: A Literature Review - Alfharizi, Zella; Kesuma, Lucky Indra; Haryanto, Dedi (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2026)
This study examines the factors influencing the success of information technology (IT) project management through a literature study approach. The high failure rate of IT projects, characterized by schedule delays, cost overruns, and unmet objectives, highlights the importance of effective project management practices. The objective of this research is to analyze and synthesize key factors that contribute to the success of IT project management based on existing academic literature. The research method employed is a literature study, involving the review and analysis of relevant national and international journals, textbooks, and scholarly publications related to IT project management. The findings indicate that several critical factors consistently influence IT project success, including comprehensive project planning, competent human resources, effective risk management, clear communication among project stakeholders, and the use of project management support tools. These factors are interrelated and collectively determine the ability of organizations to manage IT projects efficiently and effectively. The implications of this study provide a conceptual framework that can be used by practitioners to improve IT project performance and by academics as a reference for future empirical research in the field of information technology project management.